The Immunisation Dilemma – Part 3.2 - Golden, Isaac; Stranieri, Andrew; Al Nuaimat, Alia (Homœopathic Links, 2014)
An international survey was conducted to obtain evidence regarding the attitudes towards and use of homoeoprophylaxis (HP) by accredited homeopaths. Significant differences in positions taken towards and use of HP were found between respondents of different countries, as well as between members of different professional associations within the same country. Positions and use were heavily influenced by certain factors identified by the analysis. These findings will inform us of the next step in a process towards an international position statement on HP.
Keywords: Homoeoprophylaxis; Vaccination; Survey